ANALISIS PENGARUH TEMPERATUR TERHADAP KERUSAKAN STRUKTUR PERKERASAN LENTUR (Studi Kasus : di Jalan Nasional, Kota Tarakan, Kalimantan Utara) - Desy Natalia Aglesia; Latif Budi Suparma; Bambang Suhendro (Universitas Quality, 2022)
The initial research carried out was a condition survey or visual condition assessment as the basis for analysis or research, condition assessment was carried out using the Pavement Condition Index (PCI) with the results per unit segment A with fair damage classification and per unit segment B with good damage classification. From these results, further research was carried out, namely surveying the pavement temperature at several road points using a thermogun during the day and night on certain days only, on days with extreme air temperatures. The results of the study using a thermogun obtained the highest air temperature value, namely 34⁰C, pavement temperature 53⁰C, with a pavement elasticity modulus of 2,359 MPa, horizontal tensile strain 421 microstrain, vertical strain 382 microstrain. Then for the estimated service life of the remaining pavement structure with the criteria for fatigue/fatigue cracks that occur on the pavement is 1.271.093 wheel paths, and for minor cracks/permanent deformation criteria is 1.110,423 wheel paths. The results showcthat the higher the temperature, the smaller or lower the value of the elastic modulus. On the other hand, the lower the temperature, the higher the modulus of elasticity. From the mechanistic-analytic approach in this study, the estimated service life of the remaining structure can also be known.